2017
DOI: 10.1002/chem.201604516
|View full text |Cite
|
Sign up to set email alerts
|

Response Profiling Using Shotgun Proteomics Enables Global Metallodrug Mechanisms of Action To Be Established

Abstract: Response profiling using shotgun proteomics for establishing global metallodrug mechanisms of action in two colon carcinoma cell lines, HCT116 and SW480, has been applied and evaluated with the clinically approved arsenic trioxide. Surprisingly, the complete established mechanism of action of arsenic trioxide was observed by protein regulations in SW480, but not HCT116 cells. Comparing the basal protein expression in the two cell lines revealed an 80 % convergence of protein identification, but with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
2
31
0
2
Order By: Relevance
“…It was found that response profiling is applicable across diverse classes of metallodrugs, whose representatives induced specific protein regulation patterns, thus suggesting specific modes of action. 6 This method confirmed known and suggested unrecognized drug effects. Besides elucidating the modes of action of metallodrugs on a cellular level, target identification approaches emerged that frequently make use of MS-based techniques.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…It was found that response profiling is applicable across diverse classes of metallodrugs, whose representatives induced specific protein regulation patterns, thus suggesting specific modes of action. 6 This method confirmed known and suggested unrecognized drug effects. Besides elucidating the modes of action of metallodrugs on a cellular level, target identification approaches emerged that frequently make use of MS-based techniques.…”
Section: Introductionsupporting
confidence: 67%
“…The cancer cells were expanded in T25 flasks for response profiling experiments and treated with half the IC 50 -concentrations of plecstatin-2 (15 mM) or arsenic trioxide (5 mM) for 3 h. The cells were fractionated into cytoplasmic (CYT) and nuclear (NE) fractions before digestion. 6 For the PCR experiments, the cells were analogously treated with plecstatin-2 or arsenic trioxide for 24 h. Three biological replicates were used for each condition.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations